The Impacts of Collaborative Online International Learning, Web-Based Language Learning, and Onsite Learning on Japanese Language Ability - Linda, Unsriana; Dhaniar, Asmarani; Maria Tamarina, Prawati; Utari, Novella (International Journal of Engineering, Science and Information Technology, 2025)
Learning foreign languages, particularly Japanese, following Covid-2019's integration of many models and approaches. In order to increase student proficiency in learning Japanese, B University has implemented a number of learning models, including studying through traditional techniques in class face-to-face with a digital application and a collaborative online learning model. This study, which frequently employs quantitative methodologies, will have an impact on those three models and their relation to improved Japanese language proficiency. The information used comes from a survey that uses a Likert scale. The population for the raw data is drawn from 2022–2023 first- and second-semester students. These students, who responded to our survey, are Japanese Department’s students and are actively participating in three different learning environments: B-apps (web-based language learning), Collaborative Online International Learning (COIL), and regular class attendance. Our research demonstrates that B-apps has a minor impact on learning Japanese, while Collaborative Online International Learning and regular interactive class sessions are necessary to acquire deeper levels of abilities.